Technological aspects of raw wood material consumption regulation in the manufacture of window units from three-layer glued bars - Volodymyr Mayevskyy; Zoya Kopynets; Volodymyr Kovbasiuk; Yevstakhii Myskiv; Myroslava Yakuba (Наукові праці Лісівничої академії наук України, 2019)
On the basis of literature sources analysis and our experimental studies it was found that during the manufacture of window units from three-layer glued bars with double-glazed windows, a significant amount of wood waste is produced during the bar shaping. The analysis of the profiles of structural elements of window units and the technological process of their manufacture made it possible to develop the struc-ture of three-layer shaped glued bar of complex cross-section. Designs of three-layer shaped glued bars of complex cross-section for the manufacture of the window frame, window leafs and transom-bars have been developed. There are insignificant differences in the manufacturing techniques of three-layer glued bars of rectangular and shaped complex cross-sections. In particular, when forming three-layer shaped glued bars of a complex cross-section, to hold them in the stops, it is necessary to make templates from elastic material. This is important for ensuring good adhesion of these bars, taking into consideration the tolerances during the manufacture of the blanks. On the basis of the conducted experimental studies and the results of their pro-cessing, as an example, calculations of wood-waste balances (dry edged sawn timber) were carried out in the manufacture of four window units measuring 1,000 ×1,000 mm from a three-layer glued bar of rectangular cross-section and from a three-layer shaped glued bar of complex cross-section. The calculations were carried out for such structures: blank window unit; the window unit divided by transom-bar on a fixed leaf and a pivotal leaf; the window unit with two pivotal leafs; the window unit divided by transom-bar and two pivotal leafs. In a blind window unit, the glazing unit is fixed in a box with an internal profile as in the leaf. In the window unit, divided by transom-bar into a fixed leaf and a pivotal leaf, a double-glazed window in the fixed leaf at the bottom and top is additionally fixed with the help of a fixing bar and a filling rail, respectively. The analysis of wood-waste balances (dry edged sawn timber) in the manufac-ture of window units of various designs showed that the percentage of the output of window unit parts from a three-layer shaped glued bar of complex cross-section, as compared to three-layer glued bar of rectangular cross-section, increases, in particular, for a blank window unit from 27.31 to 32.73%, for a window unit divided by transom-bar into a fixed leaf and a pivotal leaf ‒ from 22.99 to 29.87%, for a window unit with two pivotal leafs ‒ from 21.65 up to 28.66%, for a window unit divided by transom-bar and two pivotal leafs ‒ from 20.95 to 29.15. In general, the use of a three-layer shaped glued bar of complex cross-section for the manufacture of window units will save up to 25.56% of dry edged pine lumber.